The Proportion of Periodontal Diseases among Type 2 Diabetes Mellitus Patients in a Selected Area of Dhaka, Bangladesh - Mahmud, Shaikh Zakir; Alif, Sheikh Mohammad; Tarafder, Monowar Ahmad; Hossain, Sarder Mahmud (Bangladesh Journal of Dental Research & Education, 2013)
This descriptive type of cross sectional study was conducted to find out the proportions of periodontal diseases among type 2 diabetes mellitus patients at National Healthcare Network (NHN) Mirpur Centre, Dhaka, Bangladesh using a pre-tested modified interviewer administrated semi structured questionnaire having purposively selected 120 samples. The study showed that 34.2% and 28.3% of the respondents were in the age group of 36 to 45 years and 46 to 55 years respectively with the mean age 46.95±10.31. Proportions of periodontitis were the highest approximately 56% followed by gingivitis was 32.5%. A highly significant association found between education level of the respondents and knowledge about cleaning teeth before going to bed and after breakfast (p=0.000). More than half of the respondents (55%) applied improper technique or method of tooth brushing followed by 39.2% applied mixed technique and the rest of 5.8% applied proper technique respectively. Although there was no significant relationship found between current smoker and periodontal diseases, chewing betel leaf was significantly associated with the occurrence of periodontal diseases (p=0.048). Multivariate logistic regression was also reveled this relationship. These periodontal diseases are multi-factorial diseases and the factors responsible for these diseases are preventable. DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16242 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 36-41